Nursing Care Interpersonal Relationship Questionnaire: elaboration and validation - José Wicto Pereira Borges; Thereza Maria Magalhães Moreira; Dalton Franscisco de Andrade (Universidade de São Paulo, 2018)
ABSTRACT Objective: to elaborate an instrument for the measurement of the interpersonal relationship in nursing care through the Item Response Theory, and the validation thereof. Method: methodological study, which followed the three poles of psychometry: theoretical, empirical and analytical. The Nursing Care Interpersonal Relationship Questionnaire was developed in light of the Imogene King's Interpersonal Conceptual Model and the psychometric properties were studied through the Item Response Theory in a sample of 950 patients attended in Primary, Secondary and Tertiary Health Care. Results: the final instrument consisted of 31 items, with Cronbach's alpha of 0.90 and McDonald's Omega of 0.92. The parameters of the Item Response Theory demonstrated high discrimination in 28 items, being developed a five-level interpretive scale. At the first level, the communication process begins, gaining a wealth of interaction. Subsequent levels demonstrate qualitatively the points of effectiveness of the interpersonal relationship with the involvement of behaviors related to the concepts of transaction and interaction, followed by the concept of role. Conclusion: the instrument was created and proved to be consistent to measure interpersonal relationship in nursing care, as it presented adequate reliability and validity parameters.